2019
DOI: 10.1136/bmjopen-2018-028550
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-traumatic stress disorder and associated factors among Koshe landslide survivors, Addis Ababa, Ethiopia: a community-based, cross-sectional study

Abstract: ObjectivesTo assess the prevalence of post-traumatic stress disorder (PTSD) and associated factors among the survivors of Koshe landslide, Addis Ababa, Ethiopia, 2018.DesignCommunity-based cross-sectional design.SettingKoshe landslide, Addis Ababa, Ethiopia.ParticipantsWe recruited 830 participants for interviews using the simple random sampling technique.MeasurementWe collected data by face-to-face interviews. The civilian version of the PTSD checklist was used to measure the symptoms of the disorder. The Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 41 publications
13
60
1
Order By: Relevance
“…However, some studies only enrolled specific age brackets (e.g., any person aged 12 to 25 [78,79], 20 to 35 [80], and 18 to 40 years) [81]. In addition, 3 studies enrolled any person aged 15 or older [82,83], 1 study enrolled any person 16 and older [69,70], and 1 study enrolled any adult aged 18 or older but restricted analyses to those aged 19 and older [84]. In addition, 1 study only enrolled adult women [85].…”
Section: Plos Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies only enrolled specific age brackets (e.g., any person aged 12 to 25 [78,79], 20 to 35 [80], and 18 to 40 years) [81]. In addition, 3 studies enrolled any person aged 15 or older [82,83], 1 study enrolled any person 16 and older [69,70], and 1 study enrolled any adult aged 18 or older but restricted analyses to those aged 19 and older [84]. In addition, 1 study only enrolled adult women [85].…”
Section: Plos Medicinementioning
confidence: 99%
“…All of the identified studies had participants whose mean age was 18 years old or older. However, 5 studies [70,79,82,83] included individuals who were younger than 18 years old, and therefore some of the data come from adolescents. However, when these studies were removed from the analyses, the results were unchanged.…”
Section: Limitationsmentioning
confidence: 99%
“…Many of the Rohingya refugees work in the refugee camps, especially as paid day laborers who help construct roads, prevent of social support was associated with poorer mental health. [39][40][41] Before the mass exodus to Bangladesh, sex-based abuse toward refugees was well documented in many reports. [4][5][6] We found that physical abuse was more frequent among male refugees than female refugees and that both physical and sexual abuse were equally prevalent among male and female refugees.…”
Section: Multivariable Analysis: Adjusted Prsmentioning
confidence: 99%
“…The prevalence rates stem from a combination of historical circumstances (e.g., war/conflicts, high criminality rates, natural disasters, etc. ; see Asnakew et al, 2019) and mental health care infrastructure within individual countries, which determines the practices related to the PTSD diagnosing and treatment.…”
Section: Introductionmentioning
confidence: 99%